Pengaruh Sikap Welas Asih Diri (Self-Compassion) pada Ketangguhan Diri (Hardiness) Dewasa Muda diperiode usia Quarter Life Crisis - Ubaidah, Ade; Nuraqmarina, Fatma (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Entering young adulthood, where the developmental task is to achieve economic and social independence, places individuals at risk of experiencing a quarter-life crisis. This period is often marked by high anxiety and stress about future uncertainties. Healthy self-hardiness is crucial for young adults to manage stress and cope with their developmental challenges. This study aims to explore the role of self-compassion in fostering hardiness among young adults during the quarter-life crisis. The research uses a quantitative cross-sectional design, employing the Multidimensional Hardiness Inventory for Young Adults, which has a reliability coefficient of α = .929. Self-compassion is measured using Neff's (2003) self-compassion scale, adapted into Indonesian with a reliability coefficient of α = .727. The hypothesis was tested using simple linear regression analysis on a sample of 116 respondents, selected through purposive sampling. The results indicate a significant positive effect of self-compassion on hardiness in young adults during the quarter-life crisis (p = .034 < .05). Developing a healthy self-compassion attitude can help young adults build hardiness, enabling them to better manage stress and achieve independence in their social and economic lives.